2016
DOI: 10.1038/srep29898
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5 expression and circulating irisin levels are modified by diet and hormonal conditions in hypothalamus, adipose tissue and muscle

Abstract: Irisin is processed from fibronectin type III domain-containing protein 5 (FNDC5). However, a controversy exists concerning irisin origin, regulation and function. To elucidate the relationship between serum irisin and FNDC5 mRNA expression levels, we evaluated plasma irisin levels and FNDC5 gene expression in the hypothalamus, gastrocnemius muscle and different depots of adipose tissue in models of altered metabolism. In normal rats, blood irisin levels diminished after 48-h fast and with leptin, insulin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 57 publications
5
55
0
Order By: Relevance
“…48 h fasting decreases blood irisin in normal rats (64). Irisin is lower in amenorrheic than in eumenorrheic athletes and non-athletes (65); however, menstrual cycle does not affect the exercise-induce response of irisin (66).…”
Section: Pre-analytical Factorsmentioning
confidence: 99%
“…48 h fasting decreases blood irisin in normal rats (64). Irisin is lower in amenorrheic than in eumenorrheic athletes and non-athletes (65); however, menstrual cycle does not affect the exercise-induce response of irisin (66).…”
Section: Pre-analytical Factorsmentioning
confidence: 99%
“…One previous study demonstrated that there is a correlation between total body adiposity and muscle FNDC5 expression, whereas obese rats paradoxically had lower circulating irisin levels (Roberts et al., ). However, another study showed that rats fed a high‐fat diet had the same plasma irisin level and muscle FNDC5 expression compared to rats fed a normal diet (Varela‐Rodriguez et al., ). In our study, we found that antroquinonol tended to increase circulating irisin and muscle FNDC5 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fibronectin type III domain containing 5 (FNDC5)/irisin is a newly identified myokine, which is related to the browning of white adipose tissue and elevation of thermogenesis (Elsen, Raschke, & Eckel, 2014). Studies showed that exercise and diet can affect FNDC5 expression and circulating irisin levels (Anastasilakis et al, 2014;Varela-Rodriguez et al, 2016). All of JFDS-2019-0488 Submitted 3/2/2019, Accepted 6/28/2019 these metabolic disorders may promote the progression of obesity pathogenesis and lead to further chronic diseases such as cardiovascular diseases and type II diabetes (Collaboration, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear why serum irisin was not associated with skeletal muscle mass in this study. Circulating irisin levels are the result of the sum of the irisin produced by different depots of adipose tissue and skeletal muscle 41 . In addition, Choi et al showed that serum irisin levels were not different between patients with sarcopenia and control subjects 42 .…”
Section: Discussionmentioning
confidence: 99%